Study on the Pottery composition of Neolithic Age in Liaoxi Area. Issue 1 (August 2021) - Gao, Shoulei; Si, Hongwei; Wu, Shuang
Abstract: The composition of 321 pieces of Neolithic pottery samples in Liaoxi Area was detected by X-ray fluorescence analyzer, and the characteristics of raw materials in different periods were analyzed by principal component analysis. The results show that the raw materials of ceramic samples are ordinary fusible clay with low SiO2 and high flux RxOy. The composition of pottery from Chahai site of Xinglongwa culture is quite different from that in other areas. The contents of Fe2 O3 and MgO are obviously higher, while the contents of SiO2, Al2 O3 and K2 O are lower. The raw materials used for making pottery are relatively poor.